KEDUDUKAN HUKUM PEKERJA OUTSOURCING PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 168/PUU-XXI/2023 - Rohendi; Nasrulloh Saipi; Ii Nadi Munajat; Ahmad Buhori (Jurnal Riset Multidisiplin Edukasi, 2025)
The practice of outsourcing in employment relations has expanded following the enactment of the Job Creation Law; however, this development has raised constitutional issues concerning the protection of workers’ rights. Constitutional Court Decision Number 168/PUU-XXI/2023 serves as a crucial milestone in reaffirming the status of outsourced workers as legal subjects who possess constitutional rights to decent work and a dignified livelihood. This study aims to analyze the legal standing of outsourced workers after Constitutional Court Decision Number 168/PUU-XXI/2023 and its implications for the state’s obligations to provide legal protection in employment law. The research employs a normative legal method using statutory, conceptual, and contemporary case approaches. The findings indicate that the Constitutional Court’s decision not only limits the flexibility of outsourcing practices but also emphasizes the active role of the state in ensuring fair, decent, and humane employment relations. The novelty of this research lies in its analysis of the Constitutional Court’s decision as a constitutional corrective instrument that shifts the outsourcing paradigm from an orientation toward economic efficiency to the protection of the constitutional rights of outsourced workers in Indonesia.